Clinical application of circulating cell-free lymphoma DNA for fast and precise diagnosis of Burkitt lymphoma: Precision medicine for sub-Saharan Africa. (13th January 2023) - Chamba, Clara; Mbulaiteye, Sam M.; Balandya, Emmanuel; Schuh, Anna
Abstract: Abstract: Burkitt lymphoma (BL) has a cure rate of around 95% when treated with chemo-immunotherapy that is standard of care in high-income countries (Minard-Colin et al., 2020, New England Journal of Medicine 382, 2207–2219), but currently, more than 50% of children and young adults with endemic BL (Epstein Barr virus driven BL) in sub-Saharan Africa (SSA) do not survive. Treatment for BL is largely free of charge, but there is limited access to reliable diagnostic services leading to significant delays and misdiagnoses. Innovations in histopathology such as whole slide imaging and the use of novel diagnostic approaches, in particular using circulating cell-free viral and/or lymphoma DNA (liquid biopsy), could increase access to timely and reliable diagnosis and improve outcomes in SSA.